2022
DOI: 10.3934/steme.2022015
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of multi-purpose quizzes to improve mathematics learning for transitional engineering students

Abstract: <p style='text-indent:20px;'>For students who are academically ineligible to enter a bachelor program in engineering but still want to upskill their knowledge in engineering, many universities provide an associate degree program in engineering to these students. The higher achievers from the associate degree program can transfer to a full degree program in engineering. Mathematics courses in such associate degree programs are often challenging to both the teachers and students due to various reasons. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Thus, institutions should maintain the minimum entrance standard for potential applicants who want to be trained as mathematics teachers. For those applicants who are academically not eligible to enter a formal tertiary program in mathematics but still keen to become a future mathematics teacher, the institution may need to adjust the curriculum to include an extra elective course in preparatory mathematics to lay the foundation for the students to smoothly progress to the formal mathematics curriculum, similar to the effort for the transitional engineering students reported recently in [21]. This arrangement of including a preparatory mathematics course does not require students to complete other non-credit preparational mathematics courses over 1-2 years before eligible to enter a formal program.…”
Section: Key Factors Affecting Study Progress Of Per-service Mathemat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, institutions should maintain the minimum entrance standard for potential applicants who want to be trained as mathematics teachers. For those applicants who are academically not eligible to enter a formal tertiary program in mathematics but still keen to become a future mathematics teacher, the institution may need to adjust the curriculum to include an extra elective course in preparatory mathematics to lay the foundation for the students to smoothly progress to the formal mathematics curriculum, similar to the effort for the transitional engineering students reported recently in [21]. This arrangement of including a preparatory mathematics course does not require students to complete other non-credit preparational mathematics courses over 1-2 years before eligible to enter a formal program.…”
Section: Key Factors Affecting Study Progress Of Per-service Mathemat...mentioning
confidence: 99%
“…In regional universities in Australia, students enrolled in many tertiary programs are diverse in age, mathematical background, study mode, time availability, and level of commitment to their learning due to various personal, family, and professional issues [19][20][21]. A typical education mathematics course offered in a semester or term at a regional university would have about 15-30 students enrolled from different geographical locations, predominantly the regional, rural and remote (RRR) areas where the regional university resides in and serves for, with a few from major cities or other regions nationwide.…”
Section: Introductionmentioning
confidence: 99%
“…It was often observed that some students would have a short period of interruptions in learning, usually one to three weeks, due to emergencies in their work or family commitments in a teaching term. The negative impact of such interruptions on their study could be mitigated through various learning supports, such as extension to the assessment, deferring examination, one-to-one online tutorial if required, and rescheduling for assessments (Guo, 2022a). However, for the few students who did not make necessary and meaningful efforts on their learning, this foundation mathematics course becomes the obstacle of overall progression in their degree study.…”
Section: Performance With Respect To Willingness To Engage With Learningmentioning
confidence: 99%
“…However, many of these people are academically ineligible to directly enter to a bachelor's program in engineering. As a result, many regional universities like Central Queensland University (CQU) in Australia provide these students with an opportunity to start with an associate degree program in engineering (ADE) (Guo, 2022a). Successful completion of such associate engineering programs not only partly meets the need of upskilling, but also allows the higher achievers to transfer to a full degree program in engineering if they wish.…”
Section: Introductionmentioning
confidence: 99%